A compact inorganic layer for robust anode protection in lithium‐sulfur batteries. Issue 2 (24th November 2019) - Yao, Yu‐Xing; Zhang, Xue‐Qiang; Li, Bo‐Quan; Yan, Chong; Chen, Peng‐Yu; Huang, Jia‐Qi; Zhang, Qiang
Abstract: Lithium‐sulfur (Li‐S) batteries are one of the most promising candidates for high energy density rechargeable batteries beyond current Li‐ion batteries. However, severe corrosion of Li metal anode and low Coulombic efficiency (CE) induced by the unremitting shuttle of Li polysulfides immensely hinder the practical applications of Li‐S batteries. Herein, a compact inorganic layer (CIL) formed by ex situ reactions between Li anode and ionic liquid emerged as an effective strategy to block Li polysulfides and suppress shuttle effect. A CE of 96.7% was achieved in Li‐S batteries with CIL protected Li anode in contrast to 82.4% for bare Li anode while no lithium nitrate was employed. Furthermore, the corrosion of Li during cycling was effectively inhibited. While applied to working batteries, 80.6% of the initial capacity after 100 cycles was retained in Li‐S batteries with CIL‐protected ultrathin (33 μm) Li anode compared with 58.5% for bare Li anode, further demonstrating the potential of this strategy for practical applications. This study presents a feasible interfacial regulation strategy to protect Li anode with the presence of Li polysulfides and opens avenues for Li anode protection in Li‐S batteries under practical conditions. Abstract : A compact inorganic layer (CIL) that can block lithium polysulfides and shuttle effect in lithium‐sulfur batteries is constructed on lithium metal anode. The CIL renders much improved Coulombic efficiency without LiNO3 additive and ensures superior cycling performance of lithium‐sulfur batteries with ultrathin lithium metal anodes.